Analisis Kebutuhan Pengembangan Media Pembelajaran Berbasis Cartoon dalam Pembelajaran IPA pada Materi Lingkungan Kelas III SD - Yamin, Muhammad Richsan; Karmila, Karmila (Biology Teaching and Learning, 2019)
Abstract. The implementation of the industrial revolution 4.0 policy had a significant impact on the achievement of several strategic fields to support government programs in advancing Indonesia primarily in the field of Education as a basis in science and supporting the technological development process in the field of Education. The 4.0 industrial revolution policy in the field of Education is used to be able to maximize learning media in supporting the learning process so that it gives an impact on the understanding of the murky and is mainly able to implement the knowledge in daily life. The use of cartoon media in the learning process is a form of progress in the field of Education, cartoon media is used as a medium in the learning process to provide interest to the murmur of elementary schools to easily understand the information conveyed through cartoon shows as a learning media in science learning, especially in discussions environment. The impact of the use of cartoon as a learning medium for elementary school students has a pretty good impact on understanding how to protect the environment, so the results of this study directly have a positive impact on the development of elementary school students thinking about the environment and ways to preserve the environment in learning Science. Keywords: learning media, cartoon, environment